Interfacial Approach toward Benzene‐Bridged Polypyrrole Film–Based Micro‐Supercapacitors with Ultrahigh Volumetric Power Density. (20th December 2019) - Jiang, Kaiyue; Baburin, Igor A.; Han, Peng; Yang, Chongqing; Fu, Xiaobin; Yao, Yefeng; Li, Jiantong; Cánovas, Enrique; Seifert, Gotthard; Chen, Jiesheng; Bonn, Mischa; Feng, Xinliang; et al.
Abstract: 2D soft nanomaterials are an emerging research field due to their versatile chemical structures, easily tunable properties, and broad application potential. In this study, a benzene‐bridged polypyrrole film with a large area, up to a few square centimeters, is synthesized through an interfacial polymerization approach. As‐prepared semiconductive films exhibit a bandgap of ≈2 eV and a carrier mobility of ≈1.5 cm 2 V −1 s −1, inferred from time‐resolved terahertz spectroscopy. The samples are employed to fabricate in‐plane micro‐supercapacitors (MSCs) by laser scribing and exhibit an ultrahigh areal capacitance of 0.95 mF cm −2, using 1‐ethyl‐3‐methylimidazolium tetrafluoroborate ([EMIM][BF4 ]) as an electrolyte. Importantly, the maximum energy and power densities of the developed MSCs reach values up to 50.7 mWh cm −3 and 9.6 kW cm −3, respectively; the performance surpassing most of the 2D material‐based MSCs is reported to date. Abstract : Benzene‐bridged polypyrrole films with controlable thickness and ultralarge area are prepared by a conventional interfacial polymerization method. Such a semiconductive polypyrrole film, which possesses a bandgap of 2.0 eV and a carrier mobility of ≈1.5 cm 2 V −1 s −1, can be used as electrode material for micro‐supercapacitors and exhibits ultrahigh energy (50.7 mWh cm −3 ) and power (9.6 kW cm −3 ) densities.